THE RELATIONSHIP BETWEEN SERUM SYPHILIS AND CRP LEVELS AND FRENCH DISEASE PERFORMANCE INDEX - BAYRAKTAR, Nihayet; BAYRAKTAR, Mustafa (Göbeklitepe Medical Science Journal, 2018)
In our country, syphilis is a bacterium called "Treponema pallidum". In recent years, we aimed to present CRP as an acute inflammatory disease with inflammation and syphilis. Materials and Methods: In this study, total (n = 425 patients with VRDL), 32 of them VRDL positive, 20 female and 12 male, VRDL and CRP values were measured in patients with VRDL and healthy subjects.Results: VRDL and CRP levels were compared according to the initial diagnosis. Serum CRP levels were significantly higher in the syphilis group than in the control group (P <0.05). Conclusion: It was concluded that serum VRDL and CRP levels were significantly associated with syphilis. According to these results; The important effect of CRP in evaluation of syphilis should be considered.